2010
DOI: 10.2174/1876817201002010060
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mRNA for Nuclear Receptor Co-Activators 1 and 3 in Archival Breast Cancer Tissue and Surrounding Stroma: A Tissue Expression Study~!2009-01-14~!2010-02-10~!2010-07-20~!

Abstract: Before the age of 75 years, approximately 10% of women will be diagnosed with breast cancer, one of the most common malignancies and a leading cause of death among women. The objective of this study was to determine if expression of the nuclear receptor coactivators 1 and 3 (NCoA1 and NCoA3) varied in breast cancer grades. RNA was extracted from 25 breast tumours and transcribed into cDNA which underwent semi-quantitative polymerase chain reaction, normalised using 18S. Analysis indicated that an expression ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…NCOA3 was selected as a suitable candidate gene due to its high impact in breast cancer in several studies including those by Burwinkel et al (2005), Smith et al (2010), Reiter et al (2001) and Anzick et al (1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCOA3 was selected as a suitable candidate gene due to its high impact in breast cancer in several studies including those by Burwinkel et al (2005), Smith et al (2010), Reiter et al (2001) and Anzick et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Research in our laboratory recently demonstrated that NCOA3 expression increases in grade 3 and oestrogen receptor alpha negative tumours, when compared to controls (Smith et al, 2010). While NCOA3 is reported to be over-expressed in many breast cancer patients, Burwinkel et al identified two SNPs 1758G N C (rs2230782) and 2880A N G (rs2076546) that appeared to have a protective effect (Burwinkel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%